Potentiation of Hepatotoxic Effects of Methotrexate by Isoniazid in Mice; an Explorative Study - Khokar, Amna (International Journal of Pathology, 2021)
Objective: To evaluate the effect of isoniazid on methotrexate induced hepatotoxicity.Study design: Laboratory-based experimental studyPlace and Duration of Study: Department of Pharmacology Army Medical College, from November 2015 to November 2016.Material and Methods: Thirty mice were randomly divided into five groups (n=6). Group Ⅰ was given 0.2 ml normal saline by intraperitoneal injection. Group Ⅱ received 0.2 ml of distilled water by oral gavage for 5 days a week for 4 weeks. Group Ⅲ received single intraperitoneal injection of methotrexate 20 mg/kg. Group Ⅳ received Isoniazid 25 mg/kg oral for 5 days a week for 4 weeks. Group Ⅴ received Isoniazid 25 mg/kg oral for 5 days a week for 4 weeks and methotrexate 20 mg/kg i.p after two weeks. Blood samples for measuring serum ALT, AST and ALP along with liver samples for hepatic histological H&E examination were taken after 24 hours of last dose.Results: Serum ALT, AST, ALP levels were significantly raised in group V (MTX + INH) higher than all other groups exhibiting significant potentiation of MTX induced hepatotoxicity by INH. Histologically group III (MTX) and group IV (INH) showed mild to moderate inflammatory changes whereas group V (MTX + INH) were graded as severe hepatotoxicity with Central vein ischemic changesConclusion: It was concluded from results that Isoniazid Potentiates Hepatotoxic effects of Methotrexate in mice as evidenced by histological changes and elevated hepatic enzymes.